Can Largemouth Bass Transplanted from an Unexploited Population Genetically Contribute to an Active Fishery? A Test Case for Genetic Management of Exploited Fish Populations. (4th March 2017) - Hessenauer, Jan-Michael; Vokoun, Jason; Welsh, Amy; Davis, Justin; Jacobs, Robert; O' Donnell, Eileen
Abstract: Recreational fishing is one of the most popular outdoor activities in the world, resulting in substantial effects on recreational fish stocks. Recent studies have found that recreational angling may drive fisheries-induced evolution, resulting in changes in the size, behavior, and physiology of exploited recreational stocks. Traditional harvest-based management of recreational fisheries may be unable to mitigate these changes, especially with the rise of catch-and-release practices for many fisheries. We explored the potential to genetically manage exploited fisheries by introducing individuals from unexploited populations as a means to mitigate selection from recreational angling. We stocked 77 individuals from an unexploited population of Largemouth Bass Micropterus salmoides and 79 individuals from an exploited population into a third water body (with an active fishery) and evaluated the extent to which each group of stocked fish contributed to fall age-0 recruits. Fifty-four percent of the sampled age-0 Largemouth Bass with reliable parentage were hybrids of stocked and resident parents. Individuals from the exploited and unexploited populations contributed to the age-0 sample in proportion to their initial abundances. No sex-biased contribution was detected between the exploited and unexploited individuals stocked into the pond, although the largest females had the highest contribution to the age-0 sample. Age-0 fish originating from hybridization between unexploited and resident parents had significantly higher condition than age-0 recruits originating from two resident parents. We conclude that individuals from unexploited populations can successfully reproduce in an exploited system and that genetic management may be a feasible option for mitigating the effects of recreational fisheries-induced evolution. Received January 12, 2016; accepted October 28, 2016 Published online February 23, 2017